(3TQM YeOI GdeLjO aj GdfXe hGdJLhjOs - (3Yde GdOjf Hf eMeO GdSNGhi GdfMhis; (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3jGef jQhe JdGhI GdbQBf hjQhO TCh CjeI GdEJbGf jQhe hjQhOg aYdGf eVGQYGf ef GdQhe GddPjf HeYfi GdWdH s
(3BNQgG (B:s
(3Chba Ydi GdLejY Ke gQhdG Chba Ydi GdKGfi ceG bO fbdG acdgG MGFQI YfO GdGOG hGdMeLO ddGdg NJekG hEHJOG s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1171s
Keywords: (3GdbQGAGJ hGdJLhjOs